Crestal bone preservation: A review of different approaches for successful implant therapy - D Krishna Prasad; Manoj Shetty; Neha Bansal; Chethan Hegde (Wolters Kluwer Medknow Publications, 2011)
The level of bone crest surrounding the implant is of utmost significance to determine osseointegrated implant success, as preservation of marginal bone height is highly important for long-term dental implant survival. Various approaches have been described in the literature to prevent the crestal bone loss, including platform switching, non-submerged approach, scalloped implants, implant design modifications, progressive loading, immediate implant placement, etc. The purpose of this paper is to review all the possible methods to preserve the crestal bone, when each method should be used and their success rates in an attempt to address this complex problem of crestal bone resorption. "PubMed" and "Google Scholar" were used to find out any studies involving platform switching concept from 1990 up to 2009. Twenty-four studies involving methods for preservation of crestal bone were evaluated, which included 26% studies on platform switching, 22% on non-submerged approach, 17% on scalloped implants, 13% on progressive loading and 22% on immediate implant placement. Crestal bone preservation should be thought of starting from the design of the implant to be placed. The technique to be followed in a given case will depend upon the density of bone, force factors by the patient, bone volume and amount of soft tissues, etc. The best possible method or the combination of the methods should be used to preserve the crestal bone for the long-term success of the implants.